Analisis Siklus Hidup Pariwisata dalam Pengembangan Pariwisata Berkelanjutan di Kawasan Wisata Lembah Harau, Kabupaten Lima Puluh Kota - Indah Andesta (JURNAL MASTER PARIWISATA, 2022)
Lembah Harau is a nature tourism park in Lima Puluh Kota Regency. Lembah Harau area has with strong potential to attract tourist both in natural attraction and man-made attraction. Concept of tourist area life cycle is used to analyze the position of Lembah Harau based on that concept and then to develop sustainable tourism in Lembah Harau. Sarosah Village is a man-made attraction in Lembah Harau. In which it has the role towards man-made and natural attraction in Lembah Harau area are needed to develop the area for sustainable tourism development. There is the strong relationship between Sarosah Village and Lembah Harau itself to bring the Lembah Harau area to rejuvenation level. Based on natural attraction, Lembah Harau area is consolidation to stagnation level. Although, the concept of Sarosah Village is difference with Lembah Harau area’s concept as a conservation area. But Sarosah Village gives the positive impact to develop Lembah Harau and Sarasah Village is following the sustainable development tourism concept. Keywords: Development, natural tourist attraction, man-made tourist attraction, tourist area life cycle.